Transforming growth factor-β1 increases lysyl oxidase expression by downregulating MIR29A in human granulosa lutein cells. Issue 3 (September 2016) - Fang, Ying; Chang, Hsun-Ming; Cheng, Jung-Chien; Klausen, Christian; Leung, Peter C K; Yang, Xiaokui
Abstract : Lysyl oxidase (LOX), a key enzyme in the formation and stabilization of the extracellular matrix, is expressed in granulosa cells and plays a critical role in the regulation of granulosa cell differentiation, oocyte maturation and ovulation. To date, the regulation of LOX expression in human granulosa cells remains largely unknown. In this study, using primary and immortalized human granulosa lutein cells, we demonstrated that transforming growth factor (TGF)-β1 (TGFB1) upregulated LOX expression and downregulated microRNA-29a (MIR29A) expression via a TGF-β type I receptor-mediated signaling pathway. Additionally, we showed that MIR29A downregulated the expression of LOX in both types of cells. Furthermore, the downregulation of MIR29A contributed to the TGFB1-induced increase in LOX expression because the inhibition of MIR29A with a MIR29A inhibitor not only reversed the MIR29A-induced downregulation of LOX but also enhanced the TGFB1-induced upregulation of LOX. Our findings suggest that TGFB1 and MIR29A may play essential roles in the regulation of extracellular matrix remodeling during the periovulatory phase.